The Dual Role of the Antibody Response Against the Flavivirus Non-structural Protein 1 (NS1) in Protection and Immuno-Pathogenesis - Reyes-Sandoval, Arturo; Ludert, Juan E. (Frontiers in Immunology, 2019)
Dengue and Zika viruses are closely related mosquito-borne flaviviruses responsible for major public health problems in tropical and sub-tropical countries. The genomes of both, dengue and zika viruses encodes ten genes that are translated into 3 structural proteins (C, prM and E) and 7 non-structural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5). The non-structural protein 1 (NS1) is a highly conserved glycoprotein of approximately 48-50 KDa. In infected cells, NS1 is found as a homodimer associated with intracellular membranes and replication complexes, serving as a scaffolding protein in virus replication and morphogenesis. NS1 is secreted efficiently from infected cells as a hexamer and is found in patient’s sera during the acute phase of the disease. NS1 detection in sera is a valuable diagnostic marker and immunization with NS1 has been shown to protect animal models from lethal challenges with dengue and zika viruses. Nevertheless, soluble NS1 has been associated with severe dengue and anti-NS1 antibodies have been reported to cross-react with host platelets and endothelial cells and thus presumably contribute to pathogenesis. Due to the implications of NS1 in arbovirus pathogenesis and its relevance as vaccine candidate, we discuss the dual role that anti-NS1 antibodies may play in protection and disease and the challenges that need to be overcome to develop safe and effective NS1-based vaccines against dengue and Zika.